Recently formed Antarctic lakes host less diverse benthic bacterial and diatom communities than their older counterparts - Kollár, Jan; Kopalová, Kateřina; Kavan, Jan; Vrbická, Kristýna; Nývlt, Daniel; Nedbalová, Linda; Stibal, Marek; Kohler, Tyler J (FEMS microbiology ecology, 2023)
Glacier recession is creating new water bodies in proglacial forelands worldwide, including Antarctica. Yet, it is unknown how microbial communities of recently formed "young" waterbodies (originating decades to a few centuries ago) compare with established "old" counterparts (millennia ago). Here, we compared benthic microbial communities of different lake types on James Ross Island, Antarctic Peninsula, using 16S rDNA metabarcoding and light microscopy to explore bacterial and diatom communities, respectively. We found that the older lakes host significantly more diverse bacterial and diatom communities compared to the young ones. To identify potential mechanisms for these differences, linear models and dbRDA analyses suggested combinations of water temperature, pH, and conductivity to be the most important factors for diversity and community structuring, while differences in geomorphological and hydrological stability, though more difficult to quantify, are likely also influential. These results, along with an indicator species analysis, suggest that physical and chemical constraints associated with individual lakes histories are likely more influential to the assembly of the benthic microbial communities than lake age alone. Collectively, these results improve our understanding of microbial community drivers in Antarctic freshwaters, and help predict how the microbial landscape may shift with future habitat creation within a changing environment.
Keywords: mikrobiota; jezera; cryosphere; cyanobacteria; Antarctic Regions; Water; 16S rDNA; Bacteria; Diatoms; climate change; Microbiota; Antarktida; Lakes; rozsivky; glacier; voda; diatom